CNN(Convolutional Neural Network) 모델을 이용한 야구 경기 영상의 동작 분류 및 검색시스템 - 박준영(Jun-Young Park); 김재승(Jae-Seung Kim); 우용태(Yong-Tae Woo) (한국컴퓨터정보학회논문지, 2021)
본 연구에서는 CNN(Convolution Neural Network) 모델을 이용하여 야구 경기 영상에서 투구나스윙과 같은 특정 영상이 출현하는 장면을 자동으로 분류하여 효과적으로 검색하는 방법을 제안한다. 또한, 특정 동작의 분류 결과와 경기 기록을 연계한 영상 장면 검색시스템을 제안한다. 제안 시스템의 효율성을 검정하기 위하여 2018년부터 2019년까지 진행된 한국프로야구 경기 영상을대상으로 특정 장면별로 분류하는 실험을 진행하였다. 야구 경기 영상에서 투구 장면을 분류하는실험에서는 경기별로 약 90%의 정확도를 보였다. 그리고 경기 영상 내에 포함된 스코어보드를 추출하여 경기 기록과 연계하는 영상 장면 검색 실험에서는 경기별로 약 80% 정도의 정확도를 보였다. 본 연구 결과는 한국프로야구 경기에서 과거 경기 영상을 체계적으로 분석하여 경기력 향상을 위한 전략 수립을 위하여 효과적으로 사용할 수 있으리라 기대한다. In this paper, we propose a method to effectively search by automatically classifying scenes in which specific images such as pitching or swing appear in baseball game images using a CNN(Convolution Neural Network) model. In addition, we propose a video scene search system that links the classification results of specific motions and game records. In order to test the efficiency of the proposed system, an experiment was conducted to classify the Korean professional baseball game videos from 2018 to 2019 by specific scenes. In an experiment to classify pitching scenes in baseball game images, the accuracy was about 90% for each game. And in the video scene search experiment linking the game record by extracting the scoreboard included in the game video, the accuracy was about 80% for each game. It is expected that the results of this study can be used effectively to establish strategies for improving performance by systematically analyzing past game images in Korean professional baseball games. KCI Citation Count: 0